SOUTHEAST ASIA: HISTORY, MODERNITY, AND RELIGIOUS CHANGE - Sumanto Al Qurtuby (Graduate Program of Pontianak Institute of Islamic Studies, 2013)
Southeast Asia or Southeastern Asia, with more than six hundred million populations, is home to millions of Buddhists, Muslims, Confucians, Protestants, Catholics, and now Pentecostals, as well as many followers of local religions and spiritual beliefs. Notwithstanding its great historical, political, cultural legacies, however, the region has long been neglected as a site for religious studies in the Western academia. Aiming at filling the gap in Asian and religious studies as well as exploring the richness of Southeast Asian cultures, this article discusses the dynamics, diversity, and complexity of Southeast Asian societies in their response to the region’s richly political, cultural, and religious traditions spanning from pre-modern era to modern one. The article also examines the “integrative revolutions” that shaped and reshaped warfare, state organization and economics of Southeast Asia, particularly in the pre-European colonial era. In addition, the work discusses the wave of Islamization, particularly since the nineteenth century, as well as the upsurge of religious resurgence that shift the nature of religiosity and the formation of religious groupings in the area. The advent of Islam, with some interventions of political regimes, had been an important cause for the decline of Hindu-Buddhist traditions in some areas of Southeast Asia, especially Indonesia, the coming of Pentecostalism has challenged the well-established mainstream Protestantism and Catholicism, especially in Indonesia and the Philippines. Keywords: history, modernity, religious change, Southeast Asia